Pengaruh Kualitas Pelayanan, Persepsi Harga, dan Promosi Terhadap Kepuasaan Pelanggan Pada Park Hotel Cawang Jakarta - andiya pingky novanda; Hairani Tarigan (Panorama Nusantara, 2022)
This study aims to determine the effect of service quality on price perceptions and promotions on customer satisfaction. The respondents of this research are Park Hotel Cawang Jakarta customers. This research method uses multiple linear regression analysis with the help of SmartPLS 3.0 the results of this study can be seen that the P Value of service quality is 0.000 P Value of price perception 0.007 while the P Value of the promotion is 0.001. it can be conluded that there is a positive and significant influence between service quality, price perception and promotion on customer satisfaction.